Neocapitalism And Resilience: The Culture Of Self-Help As A Coping And Control Mechanism - Meneses Benítez, Marilyn Yadira (Universidad Hemisferios, 2024)
This article examines how the self-help culture and the resilience discourse have taken root in contemporary societies, configuring subjectivities oriented towards the figure of a resilient, individualized, self-sufficient citizen who favors the interests of neocapitalism. In response to the demands of this model, resilience strategies designed to survive a context of continuous crisis, precariousness and uncertainty emerge. First, we analyze the current landscape of neocapitalism and the demands it imposes on individuals, emphasizing the need for continuous adaptation and the pressure for individual success. Then, it explores how self-help has penetrated the culture, becoming part of common sense. Subsequently, the resilience strategies that individuals adopt to face the challenges of neocapitalism are analyzed. Finally, the article concludes with a critical reflection on the rise of these strategies and the implications of the depoliticization of well-being and the individualization of responsibility.